Ordered by the Logos: Reconciling Ethiopian Orthodox Sacred Astronomy with Modern Heliocentric Models - Belay Sitotaw Goshu (Britain International for Academic Research (BIAR) Publisher, 2026)
The Ethiopian Orthodox Tewahedo Church (EOTC) preserves a sacred astronomy rooted in 4th-century geocentric cosmology, featuring a three-tiered universe, angelic celestial drivers, and the Tabot as terrestrial axis mundi. This tradition conflicts with modern heliocentrism, raising questions about reconciling pre‑modern liturgical cosmology with post‑Copernican astrophysics. This review evaluates the book Ordered by the Logos, which proposes reconciliation through the Logos doctrine (John 1:1‑3), distinguishing between doxological purpose (skopos) and literal wording (lexis). The review assesses theological fidelity to Ethiopian tradition, philosophical coherence, and scientific accuracy. Using comparative religious cosmology and hermeneutical analysis, the review examines the book’s treatment of Ethiopian sacred texts (Mäṣḥafä Bərhän, Qəne), patristic precedents (Basil, Cyril, Maximus), and heliocentric evidence (Copernicus‑Galileo‑Newton‑Einstein). It identifies strengths and unresolved tensions, including angelic causality and the firmament (Dəqi). The book successfully harmonizes the two cosmologies hermeneutically, showing that worship does not require a stationary Earth, only an Earth where Christ incarnated. However, it fails to provide a mechanism for angelic planetary motion without collapsing into occasionalism, and it inadequately addresses telescopic evidence (phases of Venus, stellar parallax). Recommended with caveats, as a theology of liturgical time rather than a physics textbook. Essential for Ethiopian clergy, science‑religion scholars, and students of non‑Western cosmology.